The health policy agenda : some critical questions - American Enterprise Institute for Public Policy Research; Lewin, Marion Ein. (Washington, D.C.: American Enterprise Institute for Public Policy Research, 1985)
The seven papers in this volume, commissioned under a grant to AEI from the Pew Memorial Trust, address some of the major health policy issues shaping today's rapidly changing health care environment. The papers cover timely topics that are relevant to the current debate over the future of health care financing and delivery in a world of limited resources. The changes in physician/hospital relations; the future of technology under a new government payment system; the growing problem of the nation's uninsured and underinsured; the challenge of a graying America, with the urgency to develop more rational policies regarding long-term care; the impact on states and regions of new government policies including cuts in grants-in-aid; and the ethical implications of a more restricted, market-oriented health care system are all highlighted.
Includes bibliographical references.
ne 11/05/2018
Loans
Keywords: Medical policy - lectures; Medical economics; Medical care - addresses, essays; Delivery of health care; Economics, medical - trends; Financing, government; Health policy; United States